Cosmetic camouflage in vitiligo - Sarveswari K (Wolters Kluwer Medknow Publications, 2010)
Vitiligo is not a life-threatening nor a contagious disease. But the disfigurement of vitiligo can be devastating to its sufferers, especially dark-skinned individuals. Available treatment options are disappointing and sufferers often use various forms of camouflage. Remedial cosmetic cover creams help conceal the blemish of vitiligo at least temporarily. A high concentration of pigment is incorporated into water-free or anhydrous foundations to give a color that matches the patient′s skin, thereby concealing vitiligo patches. The article highlights the content and technique of application of these creams.